A methods engineering study on the production process of Big Honey Bakeshop - Jacobe, Ruth S. (College of Engineering, 1997)
The Big Honey Bakeshop is owned and managed by Mr. And Mrs. Joey Garing. Their bakeshop can be found in Aggregado st., Quezon City. Their product line consists of different pastries and baked products like crinkles, cookie chips, oatmeal squares, macaroons, cake slices, cupcakes, and many more. The group chose to concentrate on the processes of only one product due to the time constraint given and the wide variety of products available. Crinkles proved to be the best product to choose because it is the key-profit generating product, with a weekly profit of 16,000 pesos. It is also the most mass-produced pastry and it consists 28.04 percent of total production. It also the most mass-produced pastry and it consists 28.04 percent of total production. It also has a relatively long shelf life compared to other products, and has the least number of returns. Crinkle Production has 14 processes including inspections, and completion of these processes take an average of 96.29 minutes per batch of crinkles (each batch consists of 100 pcs). From the findings, 9 main problems were identified and these are : idle time of workers, inadequate number of workers per shift, idle time of workers, poor scheduling of ovens and mixers, excessive product variety, insufficient worker training, lack of work tables, poor plant lay-out, poor packing methods. Poor scheduling of workers, can be a cause to the first three problems. The idle time of the worker consists of 30 percent of her working time. Workers are also not given enough initial training, thus resulting to problems such as inexact measurements of ingredients. Thus, an improved scheduling of workers was made with a total of 14.75 minutes off the usual 96.29 average. Another problem encountered by the group was poor plant lay-out. Since the production area is just an extension of the owner's house, space is very much limited and some fixtures can not be moved, thus limiting the improvements that can be made. However, by improving the locations of the mixers and weighing scales, packing area, raw materials and finished goods storage, and utensils rack, the total distance traveled by the worker was decreased from 28.65 m to 14.20 m. One of the main problems encountered was excessive product variety. This can be seen in the crowding of products waiting to be baked in the oven. Due to the large demand on a variety of products, production is done 24 hours a day, and 6 days a week. This production schedule causes fatigue to the workers, which can decrease their productivity or quality of work.